Beyond Logic: Ibn al-Sarrāǧ’s (d. 316/928) al-Uṣūl fī al-naḥw and the Formation of the Islamic Disciplines - Palayret, Matthieu G. S. (AUC Knowledge Fountain, 2025)
Ibn al-Sarrāǧ’s (d. 316/928) Kitāb al-Uṣūl fī al-naḥw is a seminal text in Arabic grammar, traditionally interpreted as primarily structured by Greek logic through disjunctive divisions (taqāsīm). This thesis challenges this dominant view, arguing that Ibn al-Sarrāǧ’s innovations are more comprehensively understood through his engagement with the broader intellectual context of 3rd/9th-4th/10th century Baghdad. It posits that the work reflects dynamic interactions with contemporary Islamic religious sciences (jurisprudence, legal theory, ḥadīṯ studies) and, significantly, the emerging mathematical science of algorithmics. Through close textual analysis, this study demonstrates Ibn al-Sarrāǧ’s multifaceted role in establishing grammar’s socio-intellectual autonomy and internal structure; pioneering its epistemological foundations by distinguishing discourse levels and theorising sources, paralleling the development of uṣūl al-fiqh; and, crucially, reorganising grammatical data. A central contribution of this thesis is identifying that this data reorganisation, particularly in the syntax section, relies on algorithmic and combinatorial methods that offer a more compelling explanation than an exclusive focus on taqsīm. By looking “beyond logic,” this research reveals Ibn al-Sarrāǧ not simply as an adopter of external logical frameworks, but as an innovator drawing on diverse contemporary intellectual tools to consolidate and theorise Arabic grammar, offering a nuanced understanding of his work and the intricate formation of Islamic disciplines.